2004
DOI: 10.1029/2003wr002306
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and quantifying sources of variability in temporal and spatial soil moisture observations

Abstract: [1] Soil moisture is an important component of the hydrological cycle. It is a control in the partitioning of energy and water related to evapotranspiration and runoff and thereby influences the hydrological response of an area. Characterizing the temporal and spatial distribution of soil moisture has important hydrologic applications, yet soil moisture varies in response to many processes acting over a variety of scales; the relative importance of different temporal and spatial controls on soil moisture is st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
141
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(153 citation statements)
references
References 33 publications
9
141
1
2
Order By: Relevance
“…This result is both surprising and contradicting: while the pattern of the wetness coefficient seems very similar to detailed observed soil moisture patterns at Tarrawarra, there is hardly any correlation between the individual NMM sites and the wetness coefficient. This is in line with the findings by Wilson et al (2004), who showed that even in catchments with significant topographic variability, the topographic component might not be the largest contributor to the overall spatial variance.…”
Section: Mean Soil Moisture Time Series Estimationsupporting
confidence: 81%
“…This result is both surprising and contradicting: while the pattern of the wetness coefficient seems very similar to detailed observed soil moisture patterns at Tarrawarra, there is hardly any correlation between the individual NMM sites and the wetness coefficient. This is in line with the findings by Wilson et al (2004), who showed that even in catchments with significant topographic variability, the topographic component might not be the largest contributor to the overall spatial variance.…”
Section: Mean Soil Moisture Time Series Estimationsupporting
confidence: 81%
“…This is in agreement with the common notion that soil moisture has a huge amount of spatial variability in the field [e.g. Famiglietti et al, 2008;Wilson et al, 2004;Daly and Porporato, 2005;Rodríguez-Iturbe et al, 2006;Western et al, 2002] and the observation that satellite based, continental scale, estimates of soil-moisture are highly correlated to the equivalent precipitation and evapotranspiration patterns [Liu et al, 2009].…”
Section: A Physical Frameworksupporting
confidence: 74%
“…In assessing lagged dependence, event-scale patterns were of interest rather than large-scale trends within the time series (Wilson et al, 2004). This required seasonal patterns to be addressed prior to applying the DLNM.…”
Section: Distributed-lag Nonlinear Modelmentioning
confidence: 99%